2020
DOI: 10.1007/s00262-020-02593-w
|View full text |Cite
|
Sign up to set email alerts
|

Expression of immune checkpoints and T cell exhaustion markers in early and advanced stages of colorectal cancer

Abstract: Despite recent advances in colorectal cancer (CRC) treatment, a large proportion of patients show limited responses to therapies, especially in advanced stages. There is an urgent need to identify prognostic biomarkers and/or therapeutic targets in advanced stages, aiming to improve the efficacy of current treatments. We aimed to determine prognostic biomarkers in tumor tissue and circulation of CRC patients, with a special focus on T cell exhaustion markers. We found that mRNA levels of PD-1, TIM-3, CTLA-4, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 45 publications
5
80
0
Order By: Relevance
“…35 Additionally, upregulation of immune checkpoints including PD-1, CTLA-4, and TIM-3 and alterations in transcriptional/metabolic pathways are considered as the hallmark of T cell exhaustion. 36 In concordance with these reports, we found that the majority of T-cell exhaustion markers, including the expression of PDCD1 (gene for PD-1), TOX2 and MKI67, were upregulated in the early stages of CRC, compared with advanced stages. These data evidently discriminate phenotypical and functional characteristics of CD4 + TILs in early and advanced stages of CRC.…”
Section: Discussionsupporting
confidence: 90%
“…35 Additionally, upregulation of immune checkpoints including PD-1, CTLA-4, and TIM-3 and alterations in transcriptional/metabolic pathways are considered as the hallmark of T cell exhaustion. 36 In concordance with these reports, we found that the majority of T-cell exhaustion markers, including the expression of PDCD1 (gene for PD-1), TOX2 and MKI67, were upregulated in the early stages of CRC, compared with advanced stages. These data evidently discriminate phenotypical and functional characteristics of CD4 + TILs in early and advanced stages of CRC.…”
Section: Discussionsupporting
confidence: 90%
“…Together, these data potentially implicate that CD8 + TILs in advanced stages have not only impaired activation and effector functions, but also limited capacity of cell proliferation and differentiation to memory T cells. Moreover, the downregulation of PDCD1 gene (which encodes PD-1; IC) in CD8 + TILs from advanced stages is parallel with our recent findings in bulk tumors from patients with CRC with advanced stages, 26 implicating that anti-PD-1/ PD-L1 therapies may not be effective in patients with CRC with advanced stages.…”
Section: Discussionsupporting
confidence: 76%
“… 54 Furthermore, TOX3 , T cell exhaustion marker 56 ; FOXP3 , master transcription factor for Treg differentiation 57 ; and CCR6 , chemokine receptor associated with Treg chemotaxis to tumor tissues, 58 were upregulated in advanced stages, suggesting that cytotoxic T cell dysfunction in patients with CRC with advanced stages could be associated with T cell exhaustion and CD8 + Treg differentiation. On the other hand, activation marker PDCD1 26 59 ; inflammatory cytokines IL17A, IL7F and IL22 60 , TCR stimulation-related gene HLA-DRA 61 62 ; and inducers of programmed cell death and CD8 + T cell-mediated apoptosis FASLG and TNFRSF9 , 63 64 were downregulated in advanced disease stages, suggesting that CD8 + TILs in advanced stages could be dysfunctional and may lack the capacity of inducing antitumor activities. Together, these data potentially implicate that CD8 + TILs in advanced stages have not only impaired activation and effector functions, but also limited capacity of cell proliferation and differentiation to memory T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, ICOS serves as a co-stimulatory molecule with opposing effects on T cell activation, proliferation and functionality [ 19 ]. The prognostic significance of ICs in CRC has been explored previously [ 11 , 40 ]. We identified that only CD8 + T cells expressing different ICs were found at lower levels in CRC patients with advanced stage disease.…”
Section: Discussionmentioning
confidence: 99%